1984
DOI: 10.1088/0741-3335/26/11/004
|View full text |Cite
|
Sign up to set email alerts
|

Nonlinear ion-acoustic waves and solitons in warm-ion magnetized plasma

Abstract: Finite amplitude ion-cyclotron and ion-acoustic waves and solitons propagating obliquely in a magnetized warm-ion plasma are considered using exact ion dynamics and quasi-neutrality. The effect of finite ion temperature is to decrease the amplitude of the soliton and increase its width. The behaviour of the amplitudes of ion-cyclotron and ion-acoustic waves is studied as a function of EO, where EO is

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
25
0

Year Published

2006
2006
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(25 citation statements)
references
References 13 publications
0
25
0
Order By: Relevance
“…32 This last paper, 32 in particular, explored the effect of excess superthermal particles ͑through the parameter ͒ on the behavior and characteristics of IA solitons in an unmagnetized plasma. The Sagdeev theory was later extended to cover oblique pulse propagation with respect to an ambient magnetic field, [33][34][35][36][37] but that required the assumption of quasineutrality.…”
Section: Introductionmentioning
confidence: 99%
“…32 This last paper, 32 in particular, explored the effect of excess superthermal particles ͑through the parameter ͒ on the behavior and characteristics of IA solitons in an unmagnetized plasma. The Sagdeev theory was later extended to cover oblique pulse propagation with respect to an ambient magnetic field, [33][34][35][36][37] but that required the assumption of quasineutrality.…”
Section: Introductionmentioning
confidence: 99%
“…Xue 37 studied spherical and cylindrical dust ion acoustic shock wave and observed that shock height decreases with an increase in ion temperature and that the cold ion acoustic shock wave has the largest height. Yashvir et al 38 studied the nonlinear ion acoustic waves and solitons in warm ion magnetized plasma and found that finite ion temperature decreases the amplitude of the soliton and increases its width.…”
Section: Introductionmentioning
confidence: 99%
“…[22][23][24][25][26][27]) r will have two real roots, one being at u --0 and other at some point u = u2(> 0). Also r should be positive on the interval (0, us) and negative on (u2, Umax), where Um~x = u0 is obtained from the nonzero root of r To get the shape of the travelling solitary wave one has to solve r (u) --u" numerically with suitable boundary conditions.…”
Section: Resultsmentioning
confidence: 99%
“…It has a wide range of application in geophysical as well as in laboratory plasmas [26]. In real experimental situations ions always possess some finite temperature, which has a significant effect on solitary waves [25]. In this paper our aim is to study the effect of ion drift velocity and of ion temperature on large amplitude solitary waves in a relativistic plasma.…”
Section: Introductionmentioning
confidence: 99%